Physical Activity Recommendations for Health and Beyond in Currently Inactive Populations - Eszter Füzéki (International Journal of Environmental Research and Public Health, 2018)
Widespread persistent inactivity makes continued efforts in physical activity promotion a persistent challenge. The precise content of physical activity recommendations is not broadly known, and there are concerns that the general messaging of the guidelines, including the recommendations to perform at least 150 min of at least moderate intensity physical activity per week might seem unattainable for and even actually discourage currently inactive people. Here we show that there are a myriad of ways of being physically active, and provide (in part) out-of-the-box examples of evidence based, pragmatic, easily accessible physical activity regimes below 150 min and/or with lower than moderate intensity that yield meaningful health benefits for currently inactive people.